Selection of purification condition for recombinant endoglucanase originated from goat rumen bacteria in Escherichia coli - Quy, Nguyen Thi; Duong, Nguyen Hong; Khoa, Dao Trong; Hoang Viet, Nguyen Khanh; Hai, Nguyen Khanh; Hai, Truong Nam; Huyen, Do Thi (Academia Journal of Biology, 2020)
Cellulase is an important enzyme that plays a role in cleaving β-1,4 glucoside on cellulose to release glucose, which is of economic value and can be applied in many different fields. The 1545 bp endoglucanase gene mined from goat rumen’s bacterial metagenomic data was expressed in Escherichia coli Rosetta2. In this study, the recombinant endoglucanase was purified by his-tag affinity chromatography with differrent processes, such as using phosphate buffer with or without sodium cloride, pretreatment of samples with ammonium sulphate before supplying into affinity column, using various concentration of imidazole for washing... Finally the endoglucanse was sucessfully purified by his-tag affinity column using sodium chloride-free phosphate buffer of which 150 mM and 400 mM imidazole were used for washing and enzyme elution, respectively. The resulting enzyme showed its high purity of 99%. CMC plate assay confirmed that although less active than commercial cellulase (Sigma), the recombinant cellulase hydrolyzed CMC to form a clear zone (halo) around the well. The purified enzyme is capable of using as material for further analysis.